Cross-border cooperation (CBC) strategies for sustainable development - Castanho, Rui Alexandre (Practice, progress, and proficiency in sustainability (PPPS) book series., 2020)
""This book explores new trends in border areas dynamics and management as well as how cross-border cooperation could or not influences the sustainable development"--Provided by publisher"--